2021
DOI: 10.2196/21327
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telemedicine in a Tertiary Hospital–Based Ambulatory Practice in Detroit During the COVID-19 Pandemic: Observational Study

Abstract: Background The COVID-19 pandemic, caused by SARS-CoV-2, has forced the health care delivery structure to change rapidly. The pandemic has further widened the disparities in health care and exposed vulnerable populations. Health care services caring for such populations must not only continue to operate but create innovative methods of care delivery without compromising safety. We present our experience of incorporating telemedicine in our university hospital–based outpatient clinic in one of the wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Similar to other studies, physicians in our sample were essential in providing COVID‐19 triage, 18 , 37 , 38 , 39 information and management via virtual outpatient clinics, and post‐discharge care. 40 Much like the experiences of physicians at a rural acute care hospital, many of our physicians reported that the physician‐patient relationship was not harmed by telehealth, 41 although physicians in other studies described experiencing discomfort with the lack of hands‐on assessments. 42 , 43 Participants’ desires to see telehealth as a supplement to care within the ED beyond the pandemic align with other research findings.…”
Section: Discussionmentioning
confidence: 76%
“…Similar to other studies, physicians in our sample were essential in providing COVID‐19 triage, 18 , 37 , 38 , 39 information and management via virtual outpatient clinics, and post‐discharge care. 40 Much like the experiences of physicians at a rural acute care hospital, many of our physicians reported that the physician‐patient relationship was not harmed by telehealth, 41 although physicians in other studies described experiencing discomfort with the lack of hands‐on assessments. 42 , 43 Participants’ desires to see telehealth as a supplement to care within the ED beyond the pandemic align with other research findings.…”
Section: Discussionmentioning
confidence: 76%
“…The importance of telemedicine in terms of providing care and increasing accessibility in patients with MS during the COVID-19 period has been emphasized in a recent study [ 32 ]. In addition, it has been stated that telemedicine has vital importance in pandemic situations due to possible limited staff, limited outpatient working hours, and increasing outpatient needs [ 33 ]. In this study, psychometric properties of TSUQ and TPQ were analyzed in individuals who had been undergoing a telerehabilitation program for 4 years, but more intensively for the last 6 months, by the neurology outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies illustrate that telephone surveys have been used to measure health outcomes of older adults [ 11 , 30 , 31 ]. Consequently, telephone outreach methods have been incorporated to assess the effectiveness of telemedicine [ 12 ]. In addition to assessments, health services such as cognitive behavioral therapy, peer support, and physical health evaluations have been positively received by older participants who were unable to access in-person services [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, telephone outreach methods have been incorporated to assess the effectiveness of telemedicine [ 12 ]. In addition to assessments, health services such as cognitive behavioral therapy, peer support, and physical health evaluations have been positively received by older participants who were unable to access in-person services [ 12 , 13 ]. Thus, the telephone as a modality has many possibilities to support the health and social needs of older adults.…”
Section: Introductionmentioning
confidence: 99%